Antimicrobial Activity of Thermocycled Polymethyl Methacrylate Resin Reinforced with Titanium Dioxide and Copper Oxide Nanoparticles - Rashin Giti; Kamiar Zomorodian; Maryam Firouzmandi; Zahra Zareshahrabadi; Sedigheh Rahmannasab (International Journal of Dentistry)
Aims. This study aimed to evaluate the effect of 2.5% and 7.5% copper oxide (CuO) and titanium dioxide (TiO2) nanoparticles on the antimicrobial activity of thermocycled polymethyl methacrylate (PMMA) denture base material against standard strains of yeast and bacteria species. Material and Methods. In this in vitro study, 150 disk-shaped (10 × 2 mm) specimens of heat-cured PMMA were prepared and divided into five groups (n = 30) to be reinforced with 2.5% CuO, 7.5% CuO, 2.5% TiO2, or 7.5% TiO2 nanoparticles and a control group (without nanoparticle). The specimens were thermocycled, and their antimicrobial activity was assessed against standard strains of yeast including Candida albicans and C. dubliniensis and oral bacteria species including Streptococcus mutans, S. sobrinus, S. salivarius, and S. sanguis. Data were analyzed with ANOVA and Tukey’s post hoc tests (α = 0.05). Results. Both concentrations of CuO and TiO2 nanoparticles had significant antimicrobial activity against S. salivarius, S. sanguis, and C. dubliniensis compared with the control group (P < 0.05). Significant differences existed between both 2.5% (P = 0.006) and 7.5% CuO (P = 0.005) and the control group against S. mutans. However, TiO2 groups were not significantly different from the control group against S. mutans. Concerning C. albicans, 7.5% TiO2 was the only nanoparticle with significantly higher antimicrobial activity compared with the control group (P = 0.043). Conclusions. Both concentrations of CuO and TiO2 were effective antimicrobial agents against S. salivarius, S. sanguis, and C. dubliniensis, and the concentration of CuO was effective against S. mutans. Yet, TiO2 was not much effective. Regarding C. albicans, only 7.5% TiO2 showed efficient antimicrobial activity.